The funding of political parties - Pajares Montolío, Emilio (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
Although subjected to relatively frequent changes, some very recent, legislation on political parties funding, follow in Spain a model clearly based on public contributions, based on several concepts and from various institutions, to the extent of becoming their main source of income, without their expenses being subjected to limits or prohibitions, beyond the electoral arena. Not being possible to attribute this fact to current legal provisions, which have tended to be increasingly more restrictive, the funding received from other sources is much lower, both in the form of (legal) grants, or from member fees and contributions, creating an imbalance that has important consequences on the definition of their position in the political arena. This model is completed with a control system based on the conferral to the Court of Auditors of powers to audit the annual and electoral parties accounting books, but it has been only until the recent reforms that special attention has been paid to the necessary transparency or even to the correct regulation of sanctions for violation of the rules on the matter.doi: http://dx.doi.org/10.20318/eunomia.2016.3287
Keywords: Political parties; direct and indirect public funding; election expenses; donations; public monitoring of political finance and Court of Auditors; corruption